Penerapan Metode Economic Order Quantity (EOQ) dan Re Order Point (ROP) untuk Menganalisis Kebutuhan Bahan Baku di PT Otscon Safety Indonesia (OSIN) - Agung Awaludin Sayuti; Kusnadi Kusnadi; Hamdani Hamdani (Peneliti.net, 2022)
This study aims to analyze the inventory of raw materials at PT Otscon Safety Indonesia (OSIN). This research is a quantitative descriptive using the Economic Order Quantity (EOQ) and Re Order Point (ROP) methods. The data in this study are in the form of historical raw material needs and costs related to raw materials in 2021. The data is obtained from company reports. The results obtained are known that the EOQ method has more optimal and economical results compared to current company policies. Economical raw material order size for PT. Otscon Safety Indonesia using the EOQ method, which is a total of 205,059 items with an order frequency of 6 times in one year, the total inventory cost to be issued is Rp. 6,499,671, compared to implementing the company's current policy which requires a total inventory cost of Rp. IDR 6,499,671.